Inhibition of matrix metalloproteinase-9 attenuates kidney fibrosis and cellular senescence in the transition from acute kidney injury to chronic kidney disease - Daoqi Shen; Liyu Lin; Yiqi Su; Jiarui Xu; Wuhua Jiang; Zhen Zhang; Yi Fang; Xiaoqiang Ding; Xialian Xu (Renal Failure)
Background The mechanisms underlying the progression of chronic kidney disease (CKD) following acute kidney injury (AKI) remain poorly understood. Senescent cells induce maladaptive repair have been identified as a significant contributor to CKD subsequent to AKI.Purpose The purpose of this study was to investigate the correlations between kidney fibrosis after unilateral ischemia injury and cellular senescence and explored the potential therapeutic effect of GM6001 on AKI to CKD transition.Results The study revealed a progressive increase in both fibrosis and matrix metalloproteinase 9 (MMP9) expression, peaking approximately 14 days following unilateral ischemic injury, indicating a pivotal role of MMP9 in the pathogenesis of renal fibrosis. Additionally, the research identified an elevation in markers of renal senescence over time, including SA-β-gal, P53, P21, and P16. Treatment with GM6001 demonstrated a significant reduction in both fibrosis and senescence, evidenced by decreased MMP9 expression and associated fibrotic markers, alongside improvements in cellular senescence indicators. In vitro studies further substantiated these findings, as GM6001 effectively inhibited MMP9 expression in TGF-β-stimulated HK-2 cells, reinforcing its antifibrotic and antisenescent properties and highlighting its potential as a therapeutic intervention for renal fibrosis.Conclusion The study provided compelling evidence on the role of MMP9 in the progression of renal fibrosis and the transition from AKI to CKD. The early activation of MMP9 and its association with fibrosis highlighted its potential as a therapeutic target. GM6001, through its inhibition of MMP9, offered a promising avenue for reducing both fibrosis and cellular senescence, suggesting its potential utility in ameliorating CKD.